Illocutionary Acts Performed by Meilin in “Turning Red” the Movie - Widyasari, Ketut Monica; Sukarini, Ni Wayan; Maharani, Sang Ayu Isnu (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This analysis entitled "Illocutionary Act Performed by Meilin in Turning Red the Movie," aims at determining and analysing the types of illocutionary acts and direct and indirect illocutionary acts performed by Meilin as the main character in "Turning Red." This analysis was based on qualitative research, and data was collected through the documentation method and a note-taking technique. After collecting all relevant data, the data were analysed using the descriptive qualitative method. The data source was the utterances of Meilin, the main character in "Turning Red," the movie. This article analysed the data using the types of illocutionary acts theory proposed by Searle (1979) to categorise and analyse the collected data into five groups: declarations, assertive, expressive, directives, and commissives; and the approach proposed by Yule (1996) to determine and analyse direct and indirect illocutionary acts. Based on the result of the analysis, there were only four types of illocutionary acts used by Meilin in the movie: assertive, directive, commissive, and expressive. Assertive was expressed 17 times, directive was expressed 20 times, commissive appeared 9 times, and expressive appeared 2 times. In this analysis, no declaration acts were found because there were no utterances by Meilin that contained utterances to declare something. Therefore, the analysis also found that direct speech was the type most often expressed by Meilin; it was expressed 25 times, while indirect speech was only expressed 23 times. She mostly expressed her utterances directly because that is the easiest way to communicate with the listener. Keywords: Illocutionary acts, Types of illocutionary acts, Direct and indirect acts